2011
DOI: 10.1177/1470320311426025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ramiprilat and losartan on ischemia reperfusion injury in rat hearts

Abstract: These data indicate that losartan and ramiprilat protect the heart against ischemia/reperfusion injury independently of their hemodynamic effects but in a time-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…There have been inconsistent results concerning the effects of angiotensin inhibition on infarct size in animal models of acute MI ( 1 , 2 , 3 , 17 , 22 , 23 , 24 , 25 , 26 , 27 ). In canine models, captopril administered after coronary occlusion reduced infarct size ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been inconsistent results concerning the effects of angiotensin inhibition on infarct size in animal models of acute MI ( 1 , 2 , 3 , 17 , 22 , 23 , 24 , 25 , 26 , 27 ). In canine models, captopril administered after coronary occlusion reduced infarct size ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study four weeks of pretreatment with losartan and ramiprilat decreased myocardial infarct size and ischemia-induced ventricular premature beats. 8 Therefore, in the current study both drugs are administered for four weeks so that we can be sure about their anti-ischemic effects. Other studies showed that angiotensin receptor blockers (ARBs) can modulate UCP in the mouse brown adipose tissue, 31 rat liver 32 and rat kidney.…”
Section: Discussionmentioning
confidence: 99%
“…8 Anesthesia was induced by sodium pentobarbital (50 mg/kg, intraperitoneally (i.p.)). Body temperature was monitored with a rectal probe and maintained at 37°C using a heating pad.…”
Section: Ir Protocols and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preconditioning (PC) is one of the main approaches to decrease the latter injuries. [1][2][3] Ischemic preconditioning is proved to be successive in reducing the myocardial infarction. 4,5 But as it has been mentioned, this and other techniques are not suitable in human life style.…”
Section: Short Communicationmentioning
confidence: 99%